2011
DOI: 10.1113/jphysiol.2010.201533
|View full text |Cite
|
Sign up to set email alerts
|

‘Integrative Physiology 2.0’: integration of systems biology into physiology and its application to cardiovascular homeostasis

Abstract: Since the completion of the Human Genome Project and the advent of the large scaled unbiased '-omics' techniques, the field of systems biology has emerged. Systems biology aims to move away from the traditional reductionist molecular approach, which focused on understanding the role of single genes or proteins, towards a more holistic approach by studying networks and interactions between individual components of networks. From a conceptual standpoint, systems biology elicits a 'back to the future' experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…While these reductionist approaches have represented a crucial forward step towards our understanding of the impact of physical activity on vascular cells, it is important to recognize that, by nature, they are insufficient to provide us with a wide appreciation of the complex molecular effects of exercise. As a result, there is a need to move toward more holistic and integrative molecular approaches (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these reductionist approaches have represented a crucial forward step towards our understanding of the impact of physical activity on vascular cells, it is important to recognize that, by nature, they are insufficient to provide us with a wide appreciation of the complex molecular effects of exercise. As a result, there is a need to move toward more holistic and integrative molecular approaches (26).…”
Section: Discussionmentioning
confidence: 99%
“…This program allows the unbiased construction of gene (product) networks of interacting molecules by connecting all possible differentially expressed genes and hub molecules (molecules of which the expression remains unchanged; Ref. 26). Figure 5 illustrates the top endothelial gene networks influenced by exercise training in the brachial and internal mammary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Kuster et al [12], in a porcine model of myocardial infarction studied swine at rest and during graded treadmill exercise, with the intention of recruiting the cardiac and coronary functional reserve capacity, and probing into the compensatory mechanisms responsible for the maintenance of cardiovascular homeostasis. This study showed that myocardial oxygen balance was mildly perturbed in the remodeled myocardium due to the plasticity of the post-myocardial infarction remodeled heart and coronary circulation, and that the experimental results were explored in an integrative approach in an intact porcine model.…”
Section: Left Ventricular Remodelingmentioning
confidence: 99%
“…An example of integrative approach observing at the whole system and not only to the interaction of the individual elements, is the study of the coronary control mechanisms in cardiac remodeling after myocardial infarction [12]. Kuster et al [12], in a porcine model of myocardial infarction studied swine at rest and during graded treadmill exercise, with the intention of recruiting the cardiac and coronary functional reserve capacity, and probing into the compensatory mechanisms responsible for the maintenance of cardiovascular homeostasis.…”
Section: Left Ventricular Remodelingmentioning
confidence: 99%
See 1 more Smart Citation